Ethical Norms and the International Governance of Genetic Databases and Biobanks: Findings from an International Study - Capron, Alexander Morgan; Mauron, Alexandre; Elger, Bernice Simone; Boggio, Andrea; Ganguli-Mitra, Agomoni; Biller-Andorno, Nikola (Kennedy Institute of Ethics journal, 2009)
This article highlights major results of a study into the ethical norms and rules governing biobanks. After describing the methodology, the findings regarding four topics are presented: (1) the ownership of human biological samples held in biobanks; (2) the regulation of researchers’ use of samples obtained from biobanks; (3) what constitutes “collective consent” to genetic research, and when it is needed; and (4) benefit sharing and remuneration of research participants. The paper then summarizes key lessons to be drawn from the findings and concludes by reflecting on the importance of such empirical research to inform future governance norms and practices.